Implementation of Tarbawi Exegesis in Islamic Education - Rudi Iskandar (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2025)
Tarbawi exegesis is an approach to interpreting the Qur’an that emphasizes the integration of educational values in shaping students' character and morals holistically. This study aims to explore the concept, history, sources, and implementation of Tarbawi exegesis in Islamic education. Using a qualitative approach with a library research design, this study analyzes various relevant literature to understand the role of Tarbawi exegesis in the field of education. The findings reveal that Tarbawi exegesis not only serves as a means of understanding educational values in the Qur’an but also has implications for the development of learning models, curricula, character education, and the role of families in lifelong education. In conclusion, Tarbawi exegesis balances intellectual, emotional, and spiritual intelligence in the learning process. However, its implementation still faces challenges, such as educators' limited understanding, language barriers, social changes, and a lack of policy and curriculum support. Additionally, existing studies predominantly focus on children's education, while the application of Tarbawi exegesis in lifelong learning and the digital era remains underexplored. Therefore, further research is needed to develop more effective and relevant methods to address the challenges of Islamic education in the modern era.